Konsolidasi Dana Wakaf dan Haji Berdasarkan Bukti dan Hukum Syariah - Sonjaya, Niken Ardyani; Irawan, Hengki; Umar, M Abdullah (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
In an effort to utilize Hajj funds or financial resources, Muslim economists developed the concept of waqf which can be applied in India through an inclusive and collaborative investment model. They are focused on strengthening the size of non-profit waqf funds while integrating Hajj funds within the existing legal framework in Indonesia, which includes Islamic law and licensing regulations. The results of our current research show that there is no study that clearly discusses the integration of management and investment of Hajj money from the perspective of sharia decisions and assessments. This research uses a qualitative approach with normative legal methods. In accordance with sharia principles and applicable regulations, including Law Number 1386 of 2018 concerning Hajj Financial Management and Law Number 41 of 2004 concerning Waqf, there is an opportunity to combine waqf fund investments with Hajj money, while maintaining the essence of waqf, and considering benefits, risks, security and trust. Collaboration between the Hajj Financial Management Agency and professional waqf institutions registered with the Indonesian Waqf Board will be a strategic step in developing waqf assets, especially considering that investment capacity can be increased by up to 10% in Indonesia. The recommendation from this research is that BPKH and waqf institutions in India collaborate closely for the benefit of waqf and public funds, and actively provide accurate information to the public in order to reduce the spread of wrong news regarding the current status of Hajj funds.